Sweet food preference in amyotrophic lateral sclerosis - Turner, M; Talbot, K (BMJ Publishing Group, 2017)
An elderly female developed anarthria with prominent emotionality over an 18 month period prior to specialist neurological assessment. Although tongue electromyography (EMG) was normal, corticobulbar signs were consistent with amyotrophic lateral sclerosis (ALS), a pattern which in the absence of functional impairment outside of speech and swallowing, is appropriately termed progressive bulbar palsy